1990
DOI: 10.1177/000306519003800208
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Psychiatric Residents to Psychoanalysis: A Visiting Analyst's Perspective

Abstract: The serious decline in applicants for psychoanalytic training mandates the attention of psychoanalytic educators. If students are to be drawn to psychoanalysis, creative methods must be employed to convey the vigor and excitement of work in the field. The author describes two experiences as a visiting analyst, in a university hospital psychiatric residency in which there is almost no regular exposure to psychoanalytic thinking. Because he was dissatisfied with an approach that stressed literature review and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Other authors have proposed particular ways of engaging residents in the classroom with creative teaching methods. For example, Sonnenberg (1990) discusses his experience as a visiting analyst at a residency program and the importance of demonstrating his "analytic self " to the group; this involved open discussion of his use of introspection and self-analysis. He presented some of his own clinical work and listened to residents' work with attention to unconscious conflict, resistance, and transference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have proposed particular ways of engaging residents in the classroom with creative teaching methods. For example, Sonnenberg (1990) discusses his experience as a visiting analyst at a residency program and the importance of demonstrating his "analytic self " to the group; this involved open discussion of his use of introspection and self-analysis. He presented some of his own clinical work and listened to residents' work with attention to unconscious conflict, resistance, and transference.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have demonstrated analytic principles and engaged residents using humor, surprise, and sharply delineated case material (Ingram 2006), group observation of analytic interviews (Blackman 1997;Cardoso Zoppe et al 2009), structured biomedical models applied to individual cases (Melchiode 1991), or integrative models that emphasize multiple ways of viewing the patient (Cabaniss 1998). It is helpful for residents to see how analysts use theoretical principles, how they can integrate a dynamic understanding of the patient with other treatment approaches, and how analysts use themselves and their reactions to patients in deepening their understanding (Cabaniss 1998;Cardoso Zoppe et al 2009;Sonnenberg 1990). Other techniques have been useful in enhancing psychodynamic learning, including defining learning objectives for psychodynamic psychotherapy supervision (Rojas, Arbuckle, and Cabaniss 2010) and discussing videotaped psychotherapy sessions in individual or group sessions with residents (Abbass 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In his 1973 paper, "Psychoanalytic Technique and the Ego's Capacity for Viewing Intrapsychic Activity," Gray emphasized that in the best case the goal of psychoanalysis was the promotion of self-analytic capability in the analysand (Gray 1973). Those who know my work are aware that I actively advocate for that position, and that I have done so by describing in a series of papers how that practice is a central part of my professional and personal life (Sonnenberg 1990(Sonnenberg , 1991(Sonnenberg , 1993a(Sonnenberg , 1993b(Sonnenberg , 1995. I see my own life and work as clear evidence that my analysis with Paul Gray was successful.…”
Section: A Personal Experience Of Gray As Supervisor and Analystmentioning
confidence: 99%
“…It is striking to me that I didn't recognize much of this before studying Tutter's work, because I have written about the analyst's use of selfanalysis in teaching, clinical work, research, and writing (Sonnenberg 1990(Sonnenberg , 1991(Sonnenberg , 1993a(Sonnenberg ,b, 1995, and for decades I have engaged in self-analysis regularly to enhance my performance in those areas, as well as to help me live my life as happily as possible. I have written of how conflict is reflected in the relationship between the analyst and research colleagues and research subjects (1993a), and of how the relationship of the analyst to a teacher from the past might influence clinical work in the here and now (1991).…”
Section: Sonnenberg's Account Of the Role Of Unconscious Conflict In mentioning
confidence: 99%